1999
DOI: 10.1108/01437729910268641
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying: responding with some emotional intelligence

Abstract: This article outlines some of the signs indicating bullying in the workplace as a problem within contemporary organisations. Moreover, using evidence from recent Australian Court cases, the article mentions some of the costs organisations may be faced with if they fail to address the problem. Having identified the problem, the article then suggests some solutions including legislative change and development of more co-operative workplaces. Such workplaces would deal with the problem in a problem solving, rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 13 publications
2
68
0
6
Order By: Relevance
“…Discussions about the possible link between layoffs or downsizing and workplace violence were frequent during the 1990s, however, and these factors are related to job security. A number of studies have found an association between downsizing/restructuring and bullying or occupational violence at the hands of supervisors, clients, or other workers 39,40) . Similarly, in studies of workplace violence in hospital workers, insecurity and reduced staffing levels were significant risk factors for being bullied by supervisors or being abused or assaulted by patients or their families 41) .…”
Section: Discussionmentioning
confidence: 99%
“…Discussions about the possible link between layoffs or downsizing and workplace violence were frequent during the 1990s, however, and these factors are related to job security. A number of studies have found an association between downsizing/restructuring and bullying or occupational violence at the hands of supervisors, clients, or other workers 39,40) . Similarly, in studies of workplace violence in hospital workers, insecurity and reduced staffing levels were significant risk factors for being bullied by supervisors or being abused or assaulted by patients or their families 41) .…”
Section: Discussionmentioning
confidence: 99%
“…This is no different than the executive/vice-chancellor's passing of the problems to the source of the problem to resolve! It is not surprising, therefore, that the number of cases after government legislation for stress-free working environment, including this one (also see [15,22,23,24]), demonstrated that the offending employers continued to show a disregard for the law, let alone any implementation of antiharassment recommendations. The politicians, trustees, auditors, legal community, staff, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Canadian report [21] suggested a cost to employers of $3.5bn and when the costs of wage replacement, health, and medical care were included, the costs were estimated at $16bn. See also Sheehan for the Australian experience [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland every fifth employee was a victim of workplace bullying or mental abuse in 2005. Sheehan, 1999; Bad leaders have consequences beyond their effect on followers 1 . The secondary effects of bad leadership can reflect themselves on the culture and the whole organization.…”
Section: Introductionmentioning
confidence: 99%